Government by the market? : the politics of public choice - "Self, Peter" (San Francisco, 1993)
Recent decades have seen the study of politics invaded by economic theories, methods and techniques. This book gives a concise, non- technical account of these 'public choice' theories and examines their influence upon government policies in English-speaking countries. Issues covered include slimming the state, privatising welfare and re- structuring government. Final chapters offer an alternative view of the basis of good government. This book offers a unique survey and critique of the ideas and influence of an important branch of political thought and its links with market theories.
Keywords: Social choice